THE INFLUENCE OF BUDGET SYSTEM ACCOUNTABILITY AND ACCOUNTANCY PROFESIONAL TO EVALUATION OF BUDGET GOVERNANCE - Dewi, Kurnia Sari (STMIK Dharma Wacana, 2025)
In the rapidly changing uncertain and dynamic environment characterized by limited resources, the global economic crisis imposed a new attitude to budgetary control and made it one of the leading functions of management. The management function